Equal subjects, unequal rights Indigenous people in British settler colonies, 1830-1910 - Evans, Julie; Grimshaw, Patricia 1938-; Phillips, David; Swain, Shurlee (Manchester University Press, 2003)
"This book focuses on the ways in which the British settler colonies of Australia, Canada, New Zealand and South Africa treated indigenous peoples in relation to political rights, commencing with the imperial policies of the 1830s and ending with the national political settlements in place by 1910. Drawing on a wide range of sources, its comparative approach provides an insight into the historical foundations of present-day controversies in these settler societies." "This book is written in a clear readable style, accessible at all levels from first-year undergraduates to academic specialists in the fields of Imperial and Colonial History, Anthropology and Cultural Studies."--BOOK JACKET.